ANALISIS YURIDIS HAK DAN KEWAJIBAN NOTARIS DALAM PERJANJIAN KERJASAMA REKANAN BANK - RAHMAT MULIADI (PREMISE LAW JURNAL, 2016)
The problems of the research were as follows: how about legal correlation between a Notary as a public official and a Bank, how about a Notary’s right and obligation in a cooperative agreement between a Notary and a Bank for notarial service, and how about the implementation of a cooperative agreement between a Notary and a Bank concerning a Notary’s independency. The result of the research shows that the relationship between a Notary and a Bank is based on contractual relation, a contract which is signed underhandedly which is called “Cooperative Agreement on Notarial Service”. The right and obligation of both parties is that the Bank has the right to get Notarial services in drawing up authentic deeds while the Notary has the obligation do his job according to the Bank’s interest. In its implementation, this agreement violates Article 16, paragraph 1, letter a of UUJN and Article 3, paragraph 4 of Notarial Code of Ethics, which make a Notary is not independent and takes side with the Bank Keywords: Cooperative Agreement, Notary, Bank